MEDIA PREFERENCE ON NOTE-TAKING UPON STUDENTS’ COGNITIVE PROCESS - Susanti, Luh Eka (Institut Hindu Dharma Negeri Denpasar, 2018)
Note-taking acts as a tool to provide students for identifying and understanding themost important aspects of what they are learning (Borr et al., 2012). People who take notestypically retain more information which has a positive effect on learning (Titsworth in Borret al., 2012). This study aims to investigate the preference and strategies used by the studentswhen taking note. The medium they use indicates numbers of words generated in takingthe note. There were three medium being utilized; longhand (traditional using pen andpaper), laptop and mobile phone note. This study was conducted with 27 hospitalitystudents who were learning Business English for Hotel and Tourism. Pre-test, post-test,interview, and questionnaire as well were couples of instruments used to obtain the data.The media preference they used indicates the numbers of word generated, abbreviationsand symbols, looks, accurateness with the lecture time to process the note, format of notetaking, and the result of the test.